1982
DOI: 10.1139/z82-052
|View full text |Cite
|
Sign up to set email alerts
|

Sterile matings initiate the breeding season in the bank vole, Clethrionomys glareolus. A field and laboratory study

Abstract: The start of the breeding season of overwintered female bank voles, Clethrionomys glareolus, and also the start of breeding in young of the year, was characterized by a general occurrence of sterile ovulations. Similarly, in laboratory experiments, 23 out of 42 young virgin females failed to become pregnant after the first mating, and often mated several times before becoming pregnant. The experiments indicated that the sterile ovulations were attributed to temporary sterility of the females during maturation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

1982
1982
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 0 publications
2
25
1
Order By: Relevance
“…Although the present data appear to be the first to indicate that unpaired C. gapperi sometimes ovulate, the occurrence of ovulation in unpaired, unmated female C. glareolus has been reported by both Andersson and Gustafsson (1982) and Clarke and Clulow (1973), although not by Jemiolo, Marchlewska-Koj, and Buchalczyk (1980) or Westlin and Nyholm (1982). Although the available data are incomplete, they suggest a difference between the genera, with Microtus not ovulating unless placed in relatively close contact with stimuli from males and Clethrionomys ovulating more readily in response to more remote stimuli under at least some conditions.…”
Section: Discussioncontrasting
confidence: 45%
“…Although the present data appear to be the first to indicate that unpaired C. gapperi sometimes ovulate, the occurrence of ovulation in unpaired, unmated female C. glareolus has been reported by both Andersson and Gustafsson (1982) and Clarke and Clulow (1973), although not by Jemiolo, Marchlewska-Koj, and Buchalczyk (1980) or Westlin and Nyholm (1982). Although the available data are incomplete, they suggest a difference between the genera, with Microtus not ovulating unless placed in relatively close contact with stimuli from males and Clethrionomys ovulating more readily in response to more remote stimuli under at least some conditions.…”
Section: Discussioncontrasting
confidence: 45%
“…Sterile estrus, not resulting in pregnancy, has already been observed in populations of Clethrionomys spp. in spring, and is thought to prime successful breeding (Westlin and Nyholm 1981) or to be an effect of interspecific competition with other Clethrionomys species (Ims 1985) or a sign of pregnancy failure (Clarke et al 1970). In our study, earlier maturation without breeding might have been related to the observed differences in body mass, with the females fed sunflower seeds gaining more mass than the females fed barley.…”
Section: The Influence Of Density On the Initiation Of Breedingmentioning
confidence: 49%
“…Breeding of bank voles in northern Europe extends from May to September (Kaikusalo 1972;Nyholm and Meurling 1979). The majority of animals overwinter as subadults and mature in spring (Westlin and Nyholm 1981;Tkadlec and Zejda 1998). Bank voles overwinter socially in small aggregations (Ylönen and Viitala 1985), probably to prevent heat loss in the nest during foraging bouts (Vickery and Millar 1984;Wolff 1984).…”
Section: Study Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Female bank voles, Clethrionomys glareolus, which are induced ovulators (Clarke, Clulow & Greig, 1970;Westlin & Nyholm, 1982), have several matings at the start of the breeding season that do not result in pregnancy (Westlin & Nyholm, 1982). The corpora lutea (CL) of these sterile matings differ from CL of pregnancy in that they are smaller, less luteinized (as judged from their smaller cell size) and have a short life span (Westlin & Nyholm, 1982).…”
Section: Introductionmentioning
confidence: 99%